Penggunaan Metode Tutor Sebaya dalam Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran PAI (Penelitian di SMK Sabilu El-Muhtadin, Pandeglang) - Abdul Aziz; Wasehudin, Wasehudin; Muin, Abdul (Universitas Pahlawan Tuanku Tambusai, 2025)
The main objective of this study is to investigate how peer tutoring can be used as an effective method to enhance students' motivation in learning PAI at SMK Sabilu El-Muhtadin, Pandeglang. Compared to traditional teaching methods, this approach involves students from class XI acting as tutors to their peers in class X. To gain insights into the implementation of this method, a qualitative descriptive approach and field research were conducted, which focused on the PAI teacher and the students in both classes. The research used a range of data collection techniques, including observation, interviews, and document analysis, and various data processing methods such as data collection, editing, classification, and reduction were employed. The findings of this study suggest that the implementation of peer tutoring has had a positive impact on students' learning motivation, and the teachers have successfully adopted this approach in the classroom. Furthermore, the students have demonstrated a more active involvement in the learning process, which is supported by the use of diverse teaching methods.